MIPA DAN PENDIDIKAN MIPA LPTK MENUJU PERSAINGAN ASEAN ECONOMIC COMMUNITY2015 - Budi Jatmiko (Prosiding Seminar Nasional MIPA, 2014)
Abstrak: ASEAN Economic Community (AEC), atau Masyarakat Ekonomi ASEAN (MEA) akan diberlakukan akhir tahun 2015, sedangkan kualitas Sumber Daya Manusia (SDM) Indonesia diantara SDM bangsa-bangsa Asia Tenggara (ASEAN) masih berada diurutan ke-5. Atas dasar ini, maka persaingan tenaga kerja kita di kancah MEA menjadi mengkhawatirkan, dan karena itu harus ditingkatkan kualitasnya. Untuk meningkatkan kualitas SDM kita, khususnya SDM Pendidikan MIPA dan MIPA LPTK diperlukan desain peningkatan SDM yang sesuai dengan kebutuhan SDM Pendidikan MIPA dan MIPA abad ke-21. Salah satu alternatif strategai yang dapat ditempuh, adalah dengan cara: (1) Mengimplementasikan: Standar Nasional Pendidikan Tinggi, kurikulum pendidikan MIPA dan MIPA berorientasi KKNI, pembelajaran berbasis HOT, dan kebijakan pendidikan soft skill 0 sks sebagai syarat lulus; (2) Mendorong dan memfasilitasi: studi lanjut linier, dan sertifikasi profesi Dosen; (3) Menguatkan: riset bidang pendidikan MIPA dan MIPA berbasis keunggulan Prodi, dengan hasil riset bidang MIPA mendukung bidang Pendidikan MIPA, sarana & prasarana pendukung seperti gedung dan ruang kuliah, teaching & research laboratory, laboratorium: ICT, komputer, bahasa asing, dan Perpustakaan; Pendidikan Profesi Guru MIPA; dan (4) Menyelenggarakan sertifikasi profesi internasional berkaitan dengan bidang MIPA. Dengan demikian, lulusan Pendidikan MIPA dan MIPA LPTK diharapkan menjadi berkualitas, dan mampu bersaing di kancah MEA.Kata-kata kunci: Pendidikan MIPA, MIPA, LPTK, Persaingan, MEAAbstract: ASEAN Economic Community (AEC) is going to be implemented in 2015. On the other hand, the quality of Human Resources (HR) Indonesia among Southeast Asian Nations (ASEAN) is still in rank 5. Based on this basis, our labor competition in the arena of AEC becomes alarming, and therefore there is an urgent need to improve it. To improve the quality of our human resources, particularly human resources in the Mathematics and Natural Sciences, as wellas the Mathematics and Natural Sciences Education/LPTK (Teacher Education Institutions), it is also required to design the improvement of human resources in accordance with the needs of the human resources of the Mathematics and Natural Sciences as well as the Mathematics and Natural Sciences Education into the 21st century. Some alternatives that can be undertaken are as follows: (1) Implementing the National Standards for Higher Education, i.e., the Mathematics and Natural Sciences as well as the Mathematics and Natural Sciences Education curriculums that are oriented to the KKNI, HOT-based learning, soft skills education policy zero credit for graduation requirements; (2) Encouraging and facilitating: further studies in accordance to their field of study, the Lecturer professional certification; (3) Strengthening: the Mathematics and Natural Sciences Education, as well as the Mathematics and Natural Sciences researches based on the Study Program excellence, where the research results of the Mathematics and Natural Sciences will be able to support the field of the Mathematics and Natural Sciences Education, facilities and infrastructure, such as buildings, lecture halls, teaching and research laboratories, laboratories including: ICT, computers, foreign language, and Library; Teacher Professional Education of the Mathematics and Natural Sciences; and(4) Conducting International Professional Certifications related to the field of the Mathematics and Natural Sciences. Therefore, graduates of the Mathematics and Natural Sciences, as well as the Mathematics and Natural Sciences Education/ LPTK are expected to be qualified, and able to compete in the AEC.Keywords: Mathematics and Natural Sciences Education, Mathematics and Natural Sciences, LPTK, Competition, AEC